Pelatihan Digital Food dan Beverage bagi Usaha Industri Banda Aceh Cake - Ismail; Yuslinaini; Bahruni; Fathurrahmad; Syarifuddin (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2022)
This activity aims to provide digital food and beverage training in order to increase knowledge, and implement and produce high-quality and hygienic food to consumers by utilizing various online media to grow increased income for the Banda Aceh Cake industry. The location of community service activities is carried out offline at Banda Aceh Cake on the 18th to the 22nd of November 2021. Community service activities use methods with stages of presentation, discussion, case studies, and evaluation. The results of the activity provide knowledge for participants and owners of food technology innovation by staying abreast of the development of the food industry and adapting to trends so that the technology used in the digital food and beverage industry benefits businesses and consumers, especially for Banda Aceh Cake.